Kirchliche Zeitgeschichte (20. Jahrhundert) - Hering, Rainer; Mager, Inge (Arbeiten zur Kirchengeschichte Hamburgs, 2008)
The fifth part of the "Hamburgische Kirchengeschichte in Aufsätzen" (Hamburg's church history in essays) covers Hamburg's church history in the 20th century.In addition to articles on the history of the regional church in the Weimar Republic, in the "Third Reich", in the post-war period and in the second half of the 20th century, theological outsiders, student counselling, the long road to equality of theologians, denazification, the Pedagogical-Theological Institute and practical theology are presented. The history of the Catholic Church is described in own contributions. Biographies of the regional bishops and a bibliography complete the presentation.